Pengaruh Frekuensi Kunjungan Layanan Kas Keliling Terhadap Pertumbuhan Dana Tabungan Nasabah di BPRS HIK Parahyangan Periode 2021-2025: The Effect of the Frequency of Visits to Mobile Cash Services on the Growth of Customer Savings at BPRS HIK Parahyangan for the 2021–2025 Period - Raida Rasyidah Azzakiyyah (Institut Agama Islam Persis Bandung, 2025)
This study examines the influence of mobile cash service visit frequency on the growth of customer savings funds at BPRS HIK Parahyangan, motivated by the role of mobile cash services in reaching areas with minimal banking accessibility and the suspension of mobile cash fleet operations in the Cianjur region during the 2024-2025 period. The study employs a quantitative method with a causal associative approach, using secondary monthly time series data from January 2021 to December 2025 (n = 60), analyzed through simple linear regression based on Ordinary Least Squares (OLS). Since the classical assumption tests indicated violations of linearity, heteroscedasticity, and autocorrelation, the model estimation was corrected using the Newey-West Heteroscedasticity and Autocorrelation Consistent (HAC) standard errors approach at a 10% significance level (α = 0.10). The results yielded the regression equation Y= -3628.811 + 95.28149X, with a t-statistic of 1.671 and a p-value of 0.1001, significant at the 10% level. The frequency of mobile cash service visits contributes 22.3% (R2 = 0.223) to the growth of customer savings funds, while the remaining 77.7% is explained by other factors outside the model. This study concludes that the frequency of mobile cash service visits has a positive yet marginal influence on the growth of customer savings funds at BPRS HIK Parahyangan.